Uncertainties and opportunities of sheep production in Extremadura - López Gallego F.; Espejo Díaz M. (Mediterranean livestock production: uncertainties and opportunities, 2008)
Extremadura's sheep production is one of the social-economic engines of the region. It is a productive sector that manages relevant territories linked to the conservation of the environment. Nowadays this sector has led a revolution in its production system and is working on a new organization of its verticalization capacity together with the new community frame of eco-conditions and rural development.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)